Future of Rare Diseases Research 2017–2027: An IRDiRC Perspective - Austin, C.; Cutillo, C.; Lau, L.; Jonker, A.; Rath, A.; Julkowska, D.; Thomson, D.; Terry, S.; de Montleau, B.; Ardigò, D.; Hivert, V.; Boycott, K.; et al. (2018)
Due to the remarkable global surge in activity in rare diseases research over the last six years, including contributions by the International Rare Diseases Research Consortium (IRDiRC), the Consortium's 2020 goals have been largely achieved by 2017. Though these developments are gratifying, enormous challenges remain. With this paradox in mind, IRDiRC set new global rare disease goals for the coming decade with the ultimate aim of improved health for people living with rare diseases worldwide. This article is protected by copyright. All rights reserved.